Novel Solid Electrolytes for Li-Ion Batteries: A Perspective from Electron Microscopy Studies - Ma, Cheng; Chi, Miaofang (Frontiers in Energy Research, 2016)
Solid electrolytes can simultaneously overcome two of the most formidable challenges facing current state-of-art Li-ion batteries: the severe safety issues and insufficient energy densities. On the other hand, two major limitations of solid electrolytes must be overcome before they can be implemented for practical use: the relatively slow ionic conductivity and their limited interfacial stability and conductivity with electrodes. Since ion transport in solids and their interfaces is based on a hopping mechanism from atomic sites to nearby vacancy sites or suitable interstitial sites, a prerequisite to overcome these challenges is a thorough understanding of the material’s behavior at the microscopic and/or the atomic level. Transmission electron microscopy is a powerful tool that provides the spatial resolution required. Here, we review recent electron microscopy investigations towards understanding the ion transport behavior in solid electrolyte materials and their interfaces. Specifically, three aspects of recent microscopy research will be highlighted: the influence of individual grain microstructure on ion conductivity, the contribution of grain boundaries, and the behavior of solid electrolyte/electrode interfaces. Based on these results, the perspectives for future research will be discussed.